The Effectiveness of Behavioral Counseling with Shaping Technique to Increase The Feeling Guiltywhen of The Students Did A Mistake to Their Classmate - Norma Anggraini; I Ketut Dharsana; Ni Ketut Suarni (International Conference on Technology and Educational Science)
The aims of this study is to find out the effectiveness of behavioral counseling with shaping technique to increase the feeling guilty behavior when the student did a mistake to their classmate. The type of research used in this study is quasi-experiment with pretest-posttest control group design. The Population of this study is 35 students. The method of data collection used is by questioner. The result of the analysis is (tcount0,063> ttable2,032) so that Ho is rejected and Ha is accepted. So there is a significant difference. It can be concluded that behavioral counseling with behavioral shaping technique is effective to increase the feeling guilty behavior when the student doing some mistake.